PENGARUH PRODUK DOMESTIK BRUTO DAN INFLASI TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA TAHUN 2002-2009 - Panji Kusuma Prasetyanto (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2016)
This study aims to determine (1) Effect of Gross Domestic Product on Stock Price Index (IHSG) in Indonesia Stock Exchange (BEI) in 2002 to 2009, (2) Effect of Inflation on Stock Price Index (IHSG) in Indonesia Stock Exchange (BEI) in 2002-2009. The population in this study is the price index of all shares listed on the Stock Exchange (BEI) from 1 January 2002 until 31 December 2009. The samples in this study using saturation sampling or sample census. Data collection technique used documentation techniques. Analysis of the data in this study using four types of test, namely: (1) descriptive statistics, (2) the classical assumption, (3) a regression test and (4) test the hypothesis. This study using SPSS version 17.0 for data processing. The results showed that (1) the Gross Domestic Product significant positive effect on the t-count IHSG 10.793 and 0.000 significance, (2) Inflation had no significant effect on IHSG by t-test 1.942 and 0.062 significance. Keyword : Stock Price Index (IHSG), Indonesia Stock Exchange (BEI)